Separation of tumor cells from a suspension of dissociated human colorectal carcinoma tissue by means of monoclonal antibody-coated magnetic beads - Kemmner, Wolfram A.; Moldenhauer, Gerhard; Schlag, Peter M.; Brossmer, Reinhard (Journal of immunological methods, 1992)
Dissociation of colorectal tumor tissue directly obtained at surgery yields a cell suspension which contains tumor cells, leukocytes and erythrocytes. Coupling of a murine monoclonal antibody, HEA125, specific for human epithelial cells, to magnetic beads permits positive selection of a population containing essentially only tumor cells. Removal of cells from the beads is possible by papain treatment. Negative selection of tumor cells by means of beads coated with a leukocyte binding antibody offers no advantage since dead cells and erythrocytes remain. Key words: Cell separation; Colorectal tumor cell; Tumor infiltrating leukocyte; Monoclonal antibody HEA125, epithelium specific; Immunomagnetic bead
Elektronische Reproduktion der Druck-Ausgabe 9. Februar 2012
Gesehen am 25.06.2024